Veratrilla baillonii Franch exerts anti-diabetic activity and improves liver injury through IRS/PI3K/AKT signaling pathways in type 2 diabetic db/db mice. (December 2020) - He, Cai-Jing; Ma, Li-Qun; Iqbal, Muhammad Sarfaraz; Huang, Xian-Ju; Li, Jun; Yang, Guang-Zhong; Ihsan, Awais
Graphical abstract: Highlights: The water extracts of Veratrilla baillonii Franch (WVBF) improves diabetes pathology. WVBF protects liver and kidney from injury in diabetic mice. WVBF alleviates the inflammation and oxidative stress. WVBF up-regulates IRS/PI3K/AKT/GLUT4 signaling pathways in diabetic mice. WVBF suppressed the hepatic gluconeogeness. Abstract: Veratrilla baillonii Franch ( V. baillonii ) is widely consumed as herbal tea or medicine for prevention and treatment of various disorders in the minority areas of Southwest China. In current study, the therapeutic activities of water extracts of V. baillonii (WVBF) and gentiopicroside (GP), a major bioactive compound of WVBF were investigated in db/db diabetic mice. After 6 weeks of WVBF or GP treatment, the efficacy was assessed by fasting blood glucose (FBG), oral glucose tolerance test (OGTT) and homeostasis model assessment (HOMA). The results indicated that WVBF or GP exerted anti-inflammation and anti-oxidant stress actions, and reduced the pathological damages of liver and kidney in db/db diabetic mice. The potential mechanisms were further determined, and the results displayed that IRS-1/PI3K/AKT signal pathway was involved in the anti-diabetic and hepatic protection activities of WVBF. These findings demonstrated that V. baillonii can be a good candidate for developing new anti-diabetic agents.